List of privateers in the War of the Revolution with names of their commanders ...
Manuscript volume (300 pages) of privateers in the War of the Revolution with names of their commanders.
Collection material in English.
Keywords: Privateering; United States -- History -- Revolution, 1775-1783 -- Naval operations